Pupil Diameter Changes after Anesthesia with Different Doses of Sufentanil under Ultrasound Monitoring. (14th July 2022) - Zhou, Xue-Lan; Xing, Li-Ji; Liu, Hai-Rui; Qian, Yu; Zhu, Jiang; Xie, Hong
Abstract : Objective . This study aims to observe the changes in pupil diameter (PD) after anesthesia with different doses of sufentanil with the ultrasound method and observe whether pupil contraction is correlated with hemodynamic changes and bispectral index (BIS) values. Methods . A total of 124 patients between the ages of 18–65 with ASA I–II undergoing general anesthesia for surgery were enrolled in the study. According to the sufentanil dose initially injected, they were randomly divided into groups P, S1, S2, and S3, with 31 cases in each group. Group P was injected with normal saline. Group S1 was injected with 0.2 μ g/kg of sufentanil. Group S2 was injected with 0.4 μ g/kg of sufentanil. Group S3 was injected with 0.6 μ g/kg of sufentanil. Following propofol administration and eye closure, the pupil diameter (PD) of the patients in the four groups was observed and measured by ultrasound after the loss of consciousness (T1) and within 3 min after the sufentanil injection at an interval of 30 s (30 s (T2), 1 min (T3), 1 min 30 s (T4), 2 min (T5), 2 min 30 s (T6), and 3 min (T7)). PD, systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR), and BIS values at T1–T7 were recorded. Results . The ultrasonic method was used to observe that different doses of sufentanil could make the patients' pupils contract. During anesthesia induction, the changes in PD have a positive correlation with SBP, DBP, HR, and BIS values. Conclusion . Ultrasound can become a new noninvasive method to monitor pupil changes during general anesthesia, and ultrasonic observation of pupil changes has great potential for individualized analgesia management in the perioperative period.